Socialization of Clean and Healthy Living Behavior in Students of SMP Negeri 3 Katingan Tengah - Harvianto, Yudo; Mikdar, Ujen Zenal; Ulfa, Zuly Daima; Uket, Uket; Cukei, Cukei; Wisman, Yossita; Dony, Garry William; Perdana, Jeff Agung; Hasanah, Uswatun; Siskaevia, Siskaevia; Razzi, Fahrur; Bernisa, Bernisa; Nooralamsyah, Iwan; Abdullah, Abdullah; Lestari, Tiara; Syahrullah, Adi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The Government of Indonesia through the Ministry of Health has implemented a work program called clean and healthy living behavior (PHBS). In practice, PHBS has five scopes including household arrangements, workplace arrangements, health facility arrangements, educational institution arrangements and public place arrangements. One of the socializations that can be done for the practice of clean and healthy living behavior is in the education unit or school. Based on the results of interviews with teachers, students still get very little education about clean and healthy behavior. In order to provide solutions to these problems, it is necessary to hold a socialization activity about clean and healthy living behavior. Activities carried out include joint gymnastics, material presentation, discussion, and nutritious feeding. The purpose of this activity is for students to get education and practice about the importance of clean and healthy living behavior. The conclusion of the service is that this activity has successfully provided education about students' understanding and practice of clean and healthy living behavior in daily life both at home and at school. Forms of practicing clean and healthy living behaviors include doing physical activity with sports, doing physical activities other than sports, consuming nutritious foods, and keeping the environment and yourself clean every day.